(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article analyzes the strategic role of human resources in increasing the competitiveness of the tourism industry. The author compares national and international experiences to highlight the current challenges and opportunities in Uzbekistan in this field. The study evaluates the effectiveness of systems for training, retraining, and attracting modern qualified personnel. Practical recommendations are proposed to enhance the sector’s development.